Metabolic syndrome, alcohol consumption and genetic factors are associated with serum uric acid concentration - Stibůrková, Blanka; Pavlíková, Markéta; Sokolová, Jitka; Kožich, Viktor (PloS one, 2014)
OBJECTIVE: Uric acid is the end product of purine metabolism in humans, and increased serum uric acid concentrations lead to gout. The objective of the current study was to identify factors that are independently associated with serum uric acid concentrations in a cohort of Czech control individuals. METHODS: The cohort consisted of 589 healthy subjects aged 18-65 years. We studied the associations between the serum uric acid concentration and the following: (i) demographic, anthropometric and other variables previously reported to be associated with serum uric acid concentrations; (ii) the presence of metabolic syndrome and the levels of metabolic syndrome components; and (iii) selected genetic variants of the MTHFR (c.665C>T, c.1286A>C), SLC2A9 (c.844G>A, c.881G>A) and ABCG2 genes (c.421C>A). A backward model selection procedure was used to build two multiple linear regression models; in the second model, the number of metabolic syndrome criteria that were met replaced the metabolic syndrome-related variables. RESULTS: The models had coefficients of determination of 0.59 and 0.53. The serum uric acid concentration strongly correlated with conventional determinants including male sex, and with metabolic syndrome-related variables. In the simplified second model, the serum uric acid concentration positively correlated with the number of metabolic syndrome criteria that were met, and this model retained the explanatory power of the first model. Moderate wine drinking did not increase serum uric acid concentrations, and the urate transporter ABCG2, unlike MTHFR, was a genetic determinant of serum uric acid concentrations. CONCLUSION: Metabolic syndrome, moderate wine drinking and the c.421C>A variant in the ABCG gene are independently associated with the serum uric acid concentration. Our model indicates that uric acid should be clinically monitored in persons with metabolic syndrome.
Keywords: ATP-Binding Cassette Transporters; dospělí; Regression Analysis; ABC transportér z rodiny G, člen 2; ATP Binding Cassette Transporter, Subfamily G, Member 2; kyselina močová; Female; Adult; ženské pohlaví; pití alkoholu; jednonukleotidový polymorfismus; modely genetické; Alcohol Drinking; Adolescent; Metabolic Syndrome; lidé; ABC transportéry; Polymorphism, Single Nucleotide; regresní analýza; metabolický syndrom; kohortové studie; Sex Factors; Cohort Studies; Models, Genetic; Methylenetetrahydrofolate Reductase (NADPH2); Male; Glucose Transport Proteins, Facilitative; Aged; sexuální faktory; nádorové proteiny; proteiny usnadňující transport glukosy; Neoplasm Proteins; exprese genu; lidé středního věku; senioři; mužské pohlaví; Uric Acid; Middle Aged; mladiství; Gene Expression; methylentetrahydrofolátreduktasa (NADPH2); Humans